2012
DOI: 10.1111/j.1461-0248.2012.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing antagonistic interactions cause bacterial communities to collapse at high diversity

Abstract: Biodiversity is a major determinant of ecosystem functioning. Species-rich communities often use resources more efficiently thereby improving community performance. However, high competition within diverse communities may also reduce community functioning. We manipulated the genotypic diversity of Pseudomonas fluorescens communities, a plant mutualistic species inhibiting pathogens. We measured antagonistic interactions in vitro, and related these interactions to bacterial community productivity (root colonisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
188
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(201 citation statements)
references
References 55 publications
10
188
0
3
Order By: Relevance
“…through disturbance or even competitive exclusion of functionally superior pollination service providers by inferior ones from some pollination niches, could lead to negative complementarity effects. Such increases in antagonistic interactions in simple resource environments leading to negative biodiversity effects have recently been found in bacterial biodiversity-ecosystem functioning experiments [46,50]. More complex resource environments including larger temporal and spatial scales are expected to considerably broaden the scope for complementarity effects and associated increased ecosystem functioning [18,[51][52][53].…”
Section: Discussion (A)mentioning
confidence: 99%
“…through disturbance or even competitive exclusion of functionally superior pollination service providers by inferior ones from some pollination niches, could lead to negative complementarity effects. Such increases in antagonistic interactions in simple resource environments leading to negative biodiversity effects have recently been found in bacterial biodiversity-ecosystem functioning experiments [46,50]. More complex resource environments including larger temporal and spatial scales are expected to considerably broaden the scope for complementarity effects and associated increased ecosystem functioning [18,[51][52][53].…”
Section: Discussion (A)mentioning
confidence: 99%
“…Studying the effects of anthropogenic perturbations on microbial communities may give important information about the biodiversity-ecosystem functioning relationships in fluctuating environments. In earlier studies, the relationship between bacterial diversity and ecosystem functioning was found to be positive (Hodgson et al, 2002;Bell et al, 2005) or negative (Becker et al, 2012). Complementarity among different species (Bell et al, 2005;Venail and Vives, 2013), species identity (Hodgson et al, 2002) or both the mechanisms (Eisenhauer et al, 2013) may be responsible for positive effects of diversity on ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Complementarity among different species (Bell et al, 2005;Venail and Vives, 2013), species identity (Hodgson et al, 2002) or both the mechanisms (Eisenhauer et al, 2013) may be responsible for positive effects of diversity on ecosystem functioning. On the other hand, the prevalence of antagonistic interactions is the main cause behind negative relationships (Becker et al, 2012;Foster and Bell, 2012). The impacts of abiotic stress on biodiversity-ecosystem functioning relationship of microbial systems are generally found negative (Steudel et al, 2012) or positive in some cases (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although classified as P. fluorescens, recent comparative genomics studies indicate that they belong to at least three species 41 . Forty-eight communities were assembled from the eight genotypes, covering a richness of one (each of the eight genotypes in monoculture with two replicates each), two (16 combinations), four (12 combinations) and eight genotypes (4 replicates), according to a previously published design 19 . Also, these communities span a gradient in phylogenetic relatedness (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria live in complex communities forming networks of antagonistic or facilitative interactions 18,19 , with very little being known on the dynamics of cooperative behaviours in multispecies microbial communities. Diversity does not impede cooperation per se 20 , but makes it difficult to predict using the Hamiltonian framework.…”
mentioning
confidence: 99%